A comparative study of different burning time models for the combustion of aluminum dust particles. (25th July 2016) - Bidabadi, Mehdi; Poorfar, Alireza Khoeini; Wang, Shaobin; Bengt, Sunden
Graphical abstract: The spatial distribution of particles in dust cloud: Layer n - 1 (burned particles), layer n (burning particles), and layer n + 1 (preheating particles). Highlights: A new thermal model was generated to calculate the flame speed of aluminum dust cloud. As the particle size increases, the value of flame speed decreases. With the increase of the oxygen mole fraction, the value of flame speed tends to rise. The value of flame speed in carbon dioxide is the lowest than the other oxidizers. Abstract: In the present paper combustion of micron-sized aluminum dust cloud has been studied in a quiescent reaction medium with spatially discrete sources. A new thermal model is generated to estimate the flame front speed in a lean reaction environment in different oxidizer concentrations. Different burning time models for aluminum are utilized in the generated thermal model to compare their applicability by using the existing experimental data. The model is based on conduction and radiative heat transfer mechanisms using the heat point source method. The combustion of single-particle was first studied and the solution is presented. Then the dust combustion was investigated using the superposition principle to include the effects of inter-particles. The flame propagation speed as a function of aluminum dust concentration for various particle diameters is studied and the effects of radiation heat transfer are taken into account in the governing equations. In addition, flame speed in different types of oxidizers such as air, carbon dioxide, and water vapor is investigated and nitrogen is considered as the inert gas. A reasonable agreement between the results of the numerical solution of combustion of an aluminum dust cloud and the experimental data was obtained in terms of flame propagation speed. It is found that the value of flame speed of combustion of aluminum dust particles in carbon dioxide reaction medium in a considered dust concentration and particle size, is the lowest compared to the other oxidizers.